Highly efficient adsorption and mechanism of alkylphenols on magnetic reduced graphene oxide. (November 2021) - Li, Jing; Wu, Yalin; Bai, Huahua; Wen, Xiangli; Zhou, Qingxiang; Yuan, Yongyong; Liu, Yongli; Chen, Chunmao; Guo, Libing
Abstract: The influence of alkylphenols to environment cannot be ignored, as they are common product from chemical industries and potential threat to human health. Some alkylphenols are listed as persistent toxic substances (PTS) by the United Nations Environment Programme (UNEP). In this study, the optimized magnetic reduced graphene oxide (MrGO) was synthesized by a facile solvothermal method, and investigated for adsorption of three typical alkylphenols. In neutral condition, MrGO showed extremely high adsorption capacity of three typical alkylphenols, 4-heptylphenol (4-HP), 4- tert -octylphenol (4-OP), and 4-nonylphenol (4-NP), which could reach 938.9 mg g −1 (40 °C), 987.8 mg g −1 (40 °C), and 989.7 mg g −1 (20 °C), respectively. This study revealed that the adsorption process was a heterogeneous multi-layer physical adsorption, and the adsorption rates were related to the number of unoccupied vacancies on the adsorbent surface. From batch experiments and density functional theory (DFT) calculations, the main adsorption interactions between MrGO and alkylphenols were deduced to be π–π, hydrogen-bond, and hydrophobic interactions. What's more, the different affinities of MrGO towards different targets were further distinguished and explained in detail. The wonderful stability and recyclability of MrGO made it a promising cost-effective remediation candidate. Highlights: Magnetic reduced graphene oxide exhibits excellent adsorption for target phenols. Adsorption follows pseudo-second-order kinetics and Freundlich adsorption isotherm. The strong adsorption was due to hydrogen-bond, π-π interaction and hydrophobicity.